The scope of religious group autonomy: varieties of judicial examination of church employment decisions - Billingham, P (Cambridge University Press, 2020)
The idea of “church autonomy” has risen to prominence in law and religion discourse in recent years. Defenders argue that church autonomy is essential to protecting religious freedom, while critics argue that it permits great harm. This heated dispute often obscures the fact that religious group autonomy is not all-or-nothing. Religious organizations can enjoy some autonomy without being free from all legal oversight. This article thus seeks to make progress in the debate by providing a taxonomy of kinds of judicial examination of religious organizations’ decisions—focusing on employment decisions—and normatively assessing each kind. I argue that religious groups should enjoy protection from certain kinds of examination, but other kinds are justifiable, and even required. My argument supports an approach similar to that seen in some recent European Court of Human Rights decisions, rather than the less discriminating approach of U.S. courts.